INVESTIGATION STUDY OF ELECTROCHEMICAL AND MECHANICAL PROPERTIES OF ELECTRODEPOSITED COFENI MEDIUM ENTROPY ALLOY COATING - Kurniawan Henanto, Axelino
Medium entropy alloys (MEAs) have good structural strength and corrosion resistance with potential as electrocatalysts. Fabrication of MEA coatings by electrodeposition method offers a simple, affordable, and easily applicable process for industry. However, there are factors that can affect the electrochemical and mechanical properties of fabricated MEA coatings such as electrodeposition current density, current mode, and electrolyte temperature. This study investigates the influence of these electrodeposition factors on the corrosion resistance, electrocatalytic properties, hardness, as well as wear and erosion resistance of CoFeNi as one type of MEA. CoFeNi coatings were electrodeposited under varying conditions. Four different current densities (1, 3, 6, and 10 amps-per-squared-decimeter) were tested in both direct (DC) and pulsed current (PC) modes. Experiments were conducted at both room temperature (RT) and 50°C. The Taguchi’s method L16 orthogonal array design with duplication was employed to systematically investigate these factors. Electrodeposition was done on copper and API 5L X52M steel as substrates. Substrate surface preparation was carried out by grinding, ultrasonic cleaning, degreasing, and activation. The phase composition and crystallographic structure then were characterized using X-ray diffraction (XRD) while the morphology and elemental distribution were characterized using scanning electron microscopeenergy dispersive spectrometry (SEM-EDS). The surface topography and roughness were characterized using atomic force microscopy (AFM). In addition, corrosion resistance tests were conducted in 3.5%-wt NaCl solution and the electrocatalytic properties tests were conducted in 1 M KOH solution. Vickers' hardness tests, wear tests (ASTM G99), and erosion tests (ASTM G76) were also conducted. Equiatomic and single face-centered cubic (FCC) solid solution CoFeNi coating with smooth surface is fabricated in this study. Increasing the electrodeposition current density enhances the nucleation rate of the CoFeNi coating while using PC current mode compared to DC leads to reduced current efficiency and a more uniform coating. On the other hand, electrodeposition at bath temperature of 50°C compared to RT leads to an increase in current efficiency but decreases the uniformity of the coating. At various combinations of levels, the lowest corrosion current density, the lowest hydrogen evolution overpotential, the lowest oxygen evolution overpotential, the highest hardness value, the lowest specific wear rate, and the lowest erosion value were obtained in the following order: 3.319 ?A/cm2, - 128 mV vs RHE, 324 mV vs RHE, 624 HV, 16.043×10-6 mm2/Nm, and 0.036 mm3/g.